A novel technique of STEM observation of TEM section using LVSEM and application of pathological diagnosis of renal biopsy. (21st October 2022) - Nagumo, Tasuku; Sakaue, Mari; Wakatsuki, Mone; Inoue, Yuriko; Mukai, Shumpei; Yamochi, Toshiko; Takaki, Takashi
Abstract: The usefulness of the transmission electron microscope (TEM) for pathological diagnosis is apparent. However, high operating costs and other disadvantages have limited the ability to maintain and operate a TEM. In recent years, a general-purpose benchtop low-vacuum scanning electron microscope (LVSEM), which is inexpensive and easy to operate, has been developed and is expected to be applied in electron microscopic pathological diagnosis. To date, we have previously observed TEM ultrathin sections of Immunoglobulin A (IgA) nephropathy with a benchtop LVSEM using an ultra variable-pressure detector (UVD) and a newly developed holder for observing scanning transmission electron microscope (STEM) images (UVD-STEM holder) and compared the images with those obtained with typical TEM observations. We reported the results in the 53rd Annual Meeting of the Japanese Society for Clinical Molecular Morphology and the 64th Symposium of The Japanese Society of Microscopy and discussed the validity of the methods in the pathological diagnosis of IgA nephropathy and other renal diseases. As a result, we demonstrated the potential for pathological diagnosis using benchtop LVSEM. In this study, we similarly examined typical kidney diseases such as membranous nephropathy, lupus nephritis and amyloidosis. We could obtain sufficient data for the pathological diagnosis of IgA nephropathy, membranous nephropathy and lupus nephritis. However, it is difficult to detect amyloid fibres that are characteristic of amyloidosis. The development of this method is expected to expand the possibilities for pathological diagnosis using electron microscopy, including its application to other diseases.